The impact of teachers’ leadership styles on the students’ academic achievement and behaviour in a cycle 1 government school in Dubai - ALSOORI, HAYA MOHAMMAD HUSSAIN (2023)
Education professionals must be leaders in order to succeed. Leadership approaches were evaluated in Dubai's government cycle 1 schools. A study was conducted to examine the impact of teachers' leadership on student academic success and conduct. To increase the validity and dependability of the study, the researcher used both quantitative and qualitative methodologies. In order to understand successful leadership styles that will help improve academic performance and student behavior, the researcher communicated with instructors throughout the study by implementing observations, surveys, and interviews. The study results indicate that real leaders can positively influence students' academic achievement and behavior by having a thorough understanding of the curriculum, being able to use a variety of teaching methods, establishing positive relationships with students, providing constructive feedback, and letting students share their ideas and innovate.